Volume 7: 27th International Conference on Design Theory and Methodology 2015
DOI: 10.1115/detc2015-46502
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Evoked Hardness of Design Problems Using Transient Microstates

Abstract: Direct interfacing of computers with the human brain is one of the holy grails of computer science and has been in the computing folklore since the very beginning of computing history. The challenges researchers are facing are non-trivial and the breakthroughs are non-negligeable. Measuring the hardness of a mental task is a fundamental problem in design sciences. In this context, the relationship between electroencephalograms (EEG) signals and the design process is an area of research with applications to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Previous research has found that engineering design induces mental stress in students (Zhu et al 2007; Petkar et al 2009; Nguyen et al 2013; Nguyen & Zeng 2014, 2017; Nolte & McComb 2020, 2021) that persists even after the design task has ended (Nguyen & Zeng 2017). A detailed discussion on how stress might manifest during specific stages of the engineering process relevant to this study is included in Nolte & McComb (2021).…”
Section: Relevant Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has found that engineering design induces mental stress in students (Zhu et al 2007; Petkar et al 2009; Nguyen et al 2013; Nguyen & Zeng 2014, 2017; Nolte & McComb 2020, 2021) that persists even after the design task has ended (Nguyen & Zeng 2017). A detailed discussion on how stress might manifest during specific stages of the engineering process relevant to this study is included in Nolte & McComb (2021).…”
Section: Relevant Literaturementioning
confidence: 99%
“…Engineering design is a highly cognitive process (Dym et al 2005) that can induce stress for designers (Zhu, Yao & Zeng 2007; Petkar et al 2009; Nguyen, Xu & Zeng 2013; Nguyen & Zeng 2014, 2017; Nolte & McComb 2020, 2021). The multiple skills designers must use to solve design problems (e.g., analytical and technical skills, decision-making and creativity; Dym et al 2005) and the inherent complexity of design problems (e.g., ill-defined and constantly evolving; Dym et al 2005) contribute to the cognitive stress of engineering design.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This stream of studies has so far reached maturation in Nguyen et al (2019), in which EEG-based algorithms are tested against manual segmentation of design activities. The most effective algorithm in terms of predicting design segments, based on microstate transitions already discussed in Nguyen et al (2015), is almost indistinguishable than manual segmentation if specific statistical tools are used. However, because of the identification of different cognitive structures, algorithmic segmentation cannot be considered as a replacement for manual segmentation hitherto.…”
Section: Experiments Classified As "Alternative"mentioning
confidence: 99%
“…Still with reference to conceptual design, Nguyen et al (2018) use EEG to assess effort, fatigue, and concentration. Such an assessment is enabled by the results of previous scholars' studies and markedly (Nguyen et al, 2015). Based on the outcomes of the experiment, "high levels of effort occur mostly at the beginning and at the end of the design process", while some nuances of fatigue have a negative correlation with this pattern.…”
Section: Experiments Classified As "Alternative"mentioning
confidence: 99%